An orthodontic perspective on Larsen syndrome - Madoka Yasunaga; Hiroyuki Ishikawa; Kenichi Yanagita; Sachio Tamaoki (BMC, 2021)
Abstract Background Larsen syndrome (LS) is a rare disorder of osteochondrodysplasia. In addition to large-joint dislocations, craniofacial anomalies are typical characteristics. In this report, we performed orthodontic analyses, including skeletal and occlusal evaluations, to examine whether the craniofacial skeletal morphology leads to the craniofacial anomalies in LS. Case presentation A 5 year old Japanese girl who was clinically diagnosed with LS was referred to the orthodontic clinic in the Fukuoka Dental College Medical and Dental Hospital because of a malocclusion. Clinical findings at birth were knee-joint dislocations, equinovarus foot deformities, and cleft soft palate. The patient showed craniofacial anomalies with hypertelorism, prominent forehead, depressed nasal bridge, and flattened midface. To evaluate the craniofacial skeletal morphology, cephalometric analysis was performed. In the frontal cephalometric analysis, the larger widths between bilateral points of the orbitale were related to hypertelorism. The lateral cephalometric analysis revealed the midface hypoplasia and the retrognathic mandible. These findings were responsible for the flattened appearance of the patient's face, even if the anteroposterior position of the nasion was normal. Her forehead looked prominent in relation to the face probably because of the retrognathic maxilla and mandible. Both the study model and the frontal cephalometric analysis indicated constriction of the upper and lower dental arches. The posterior crossbite facilitated by the premature contacts had developed in association with the constriction of the upper dental arch. Conclusions This patient had some craniofacial anomalies with characteristic appearances in LS. It was evident that the underlying skeletal morphology led to the craniofacial dysmorphism.